Hydrogen emissions from hydrothermal fields in Iceland and comparison with the Mid-Atlantic Ridge. (28th February 2022) - Combaudon, Valentine; Moretti, Isabelle; Kleine, Barbara I.; Stefánsson, Andri
Abstract: Hydrogen emissions from geothermal systems are well known, for example associated with mafic and ultramafic rock formations along mid-ocean ridges (MOR). Here we report concentrations and emissions for H2 from geothermal fields in Iceland that provides the only MOR on Earth that exposes a largely submarine rift on land and compare them with submarine vent systems along the mid-Atlantic Ridge (MAR). The concentrations of H2 in Icelandic hydrothermal fluids are 0.022–20.5 mmol/kg comparable to H2 concentrations in MAR hydrothermal fluids of 0.07–26.5 mmol/kg. According to geochemical modeling, the H2 is considered to form in these settings associated with chemical reactions of primary mineral leaching, Fe +II to Fe +III oxidation and secondary mineral precipitation and reduction of water to hydrogen. The main factors influencing these reactions are rock type and source water composition. Geothermal power plants in Iceland emit in total ∼1.2 kt H2 per year (2019–20) or on average ∼0.7 g/MWh. The H2 is today emitted to the atmosphere but could in principle be utilized given technical aspects of such extraction are implemented. Graphical abstract: Image 1 Highlights: Large quantities of H2 are present in the fumaroles and the steam of the power plants of Iceland. The higher values are found along the active volcanic zone. The salinity and the type of water influence the H2 generation from the mafic and ultra-mafic rocks. If we consider a price of H2 of 2€/kg, the native H2 emitted by the existing power plants corresponds to 2.3 million €/yr.